Haunted by your touch - Frost, Jeaniene; Black, Shayla; Kohler, Sharie (New York : Pocket Star Books, 2010)
Three authors team up for a collection of original novellas featuring fallen angels, anarchistic demons, warrior wizards, and irresistibly dangerous creatures of the night.
Night's darkest embrace / Jeaniene Frost -- Mated / Shayla Black -- Darkest temptation / Sharie Kohler.
Keywords: Occult fiction; Love stories